The Muslims of India and the First World War 1914-1918 - Begum, Imrana (International Journal of Humanities and Social Science Research, 2019)
The years 2014-2018 marks the centenary of the World War I which was practically fought in Europe but left deep imprints beyond the European boarders and indirectly involved the whole world. At that time India was the largest British colony having about one fourth Muslim population from whom British snatched power and being ruled by the British also took part in the war. Hindus and Muslims were the two major communities of India and when the war broke out both pledged loyalty to the British. The defeat of Turkey left Indian Muslims into confusion and consternation. Being the only surviving Muslim empire, ruling large Christian population and ostensibly capable of resisting Europe, Turkey had been the pride of the Muslims. Turkey, being a symbol of the worldly power of Islam and the seat of its ‘universal’ caliphate, provided common platform to the Muslims. Turkey had also given the feelings of security to the Indian Muslims in the midst of the Hindu majority. The spirit of cooperation and loyalty with the British that had been so evident at the beginning of the World War I was wholly destroyed at the end of the War and the stage was set for a protracted struggle. The War instigated organized movements for the independence of India. The Indian Muslims launched a movement at the end of the WWI Known as Khilafat* (Caliphate) movement for the protection of the institution of Caliphate. The anti-British nature of this movement got full support of Gandhi, who advocated political agitation on a massive scale. The Hindu-Muslims alliance and the Khilafat movement ended in 1922. Although the movement did not achieve its goals and Caliphate was abolished in Turkey but it united the Muslims of India against British for the first time for their own cause. The British promises with the Indian Muslims during WWI regarding the protection of the institution of Caliphate, and the dismemberment of Turkey after the War;replacement of pan-Islamism with western nationalism;birth of modern and secular Turkey opened new avenues of thinking for the Muslims of India. The feeling of distrust and insecurity made inroads among Indian Muslims that paved the way for political transformation of India. In the post war period by passing through different crisis the Indian Muslims envisioned their future. Nationalism emerged as a strong phenomenon and on the basis of being a separate nation from Hindus they demanded a separate homeland that eventually led to the creation of Pakistan. The paper delves the history of the Muslims in India and their association with the central institution of Caliphate. It focuses the First World War and its impact on the Muslims of India specifically after the defeat of Turkey. It deals with the post war developments when Muslims became susceptible about their future in united India. It examines the Khilafat (Caliphate) movement which later on became the basis of independence movement of Indian Muslims and creation of Pakistan